iPET: The Design, Development, and Assessment of a Web-Based Application for Pet Adoption - James E. Gatmaitan; Dan Victor P. Azurin; Jhon Patrick T. Saclolo; John Albert G. Yango; Keanu P. Lorenzo; Cris Norman P. Olipas; Rachel T. Alegado (Formosa Journal of Computer and Information Science, 2024)
The iPet web application was developed to assist in pet adoption and support for pets whose owners are unable to care for them, thereby reducing the risk of abandonment. This study utilized a developmental research method, following the six steps of the waterfall model: requirements analysis, design, implementation, testing, deployment, and maintenance. IT experts used ISO 25010 standards to evaluate the application's functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. Feedback from end-user respondents in Barangay Aduas Norte, Cabanatuan City, including both pet owners and non-pet owners, indicated a high level of satisfaction with iPet's effectiveness. Based on the study's findings, recommendations were made to enhance the application. It was suggested to develop iPet as a mobile-based application for convenient access on smartphones and tablets. The integration of chat features was also recommended to improve user communication and information exchange. Future researchers were advised to utilize these findings for their own research on pet adoption applications. Implementing these recommendations would improve the functionality, user experience, and efficiency of iPet, thereby facilitating the pet adoption process and enhancing the overall experience for pet owners and potential adopters